Perlindungan Hukum terhadap Perempuan Korban Kekerasan Seksual dalam Rumah Tangga: Studi Putusan Nomor 44/Pid.Sus/2022/Pn Kng - Hanna Noviana; Rahmiati; Eprina Mawati Br. Siboro (Jurnal Hukum Lex Generalis, 2026)
Legal protection for women with mental disabilities who experience sexual violence in domestic settings requires both criminal accountability and victim recovery. This normative legal study applies statutory and case approaches to Decision Number 44/Pid.Sus/2022/PN Kng. Law Number 23 of 2004 on the Elimination of Domestic Violence is treated as the legal basis applicable to the case, while Law Number 3 of 2026 on Witness and Victim Protection, Law Number 20 of 2025 on the Criminal Procedure Code, Law Number 8 of 2016 on Persons with Disabilities and Law Number 12 of 2022 on Sexual Violence Crimes are used as current evaluative standards for victim protection. The findings show that the decision provided repressive protection through punishment and recognized the victim's vulnerability in the evidentiary assessment. However, the judicial reasoning did not expressly address the victim's rights and restitution, assistance, psychological rehabilitation and social recovery were not incorporated into the operative part of the judgment. Under the current legal framework, victim protection should include security, information, assistance, disability accommodation, restitution and sustained recovery.